Application of fractional laser in the treatment of scars - Paulina Szczepanik-Kułak; Małgorzata Michalska-Jakubus; Marta Niewiedzioł; Dorota Krasowska (Termedia Publishing House, 2020)
Scars are formed when a defect in the dermis is replaced with fibrous connective tissue. Sometimes scars limit the range of motion as a result of contractures. In addition, they are a source of severe subjective complaints and a significant cosmetic defect. People with visible scarring have been shown to have a reduced quality of life due to a sense of shame, anxiety, and the lack of public acceptance. The therapy of scars can be challenging, and may be associated with a risk of recurrence. Fractional laser treatments are currently a widely used therapeutic approach for scar management, both in paediatric and adult patients. The observed improvement in skin colour, decrease in tissue tension, and reduction of itching and pain experienced by the patient, combined with a low risk of adverse effects, determine the efficacy and safety of this treatment modality, and contribute to the satisfaction of patients with the final cosmetic result, thus improving their mental and emotional well-being.